Optimalization of Solid Waste Transportation in Geger District, Madiun - Rhenny Ratnawati; Aulia Nur Febrianti; Triana Triana (Journal of Science and Engineering, 2026)
This study aims to evaluate the performance of the solid waste transportation system in Geger District and determine the required transportation capacity to improve service coverage. The research involved the collection of primary and secondary data, including waste generation rates, transportation routes, and fleet characteristics (type, capacity, service area, and quantity). Fielad observations were conducted to quantity waste accumulation at temporary disposal sites, while fleet operational duration was analyzed through direct vehicle tracking. The performance assessment indicates that the current waste collection and transportation coverage is only 7.45%, demonstrating a significant gap between service capacity and waste generation. Operational analysis reveals inefficiencies in fleet utilization and routing. System optimization was conducted by estimating the required number of transportation units based on waste generation and service demand. Furthermore, a SWOT analysis was applied to formulate strategic improvements. The results suggest that enhancing fleet capacity, optimizing operational schedules, and improving TPS infrastructure are critical to increasing system performance. These findings provide a technical basis for developing a more efficient and sustainable solid waste transportation system in Geger District.